New Cretaceous soldier beetle (Cantharidae) from Burmese amber with preserved coloration on the elytra - Ellenberger, Sieghard; Fanti, Fabrizio (Zootaxa, 2019)
In this paper, we describe a new genus and species of soldier beetles from Burmese amber, Elektrokleinia picta gen. et. sp. nov., characterized by triangular shape of the head behind the eyes, by the elytra not covering two urites and the last urite being concave at its apex. Additionally, this new specimen shows remarkable color preservation (black-blue) on the elytra, rarely present in amber or seen on fossil soldier beetles. This coloration with metallic nuances is here considered an aposematic character.